Tromboprofilaxis en pacientes médicos hospitalizados. ¿A todos por igual? - Gazitúa P., Raimundo; Saavedra G., Silvana; Conte L., Guillermo; Figueroa M., Gastón (Revista Hospital Clínico Universidad de Chile, 2015)
Venous thromboembolic disease is the leading preventable cause of hospital mortality. Up to 75% of these are in non - surgical patients. This is a large, heterogeneous group of patients; so to know the risk factors ase is the leading preventable cause of hospital mortality. Up to 75% of these are in non - surgical patients. This is a large, heterogeneous group of patients; so to know the risk factors for deep venous thrombosis crucial to provide a correct prevention. This article reviewed the indications, contraindications and complications of thromboprophylaxis. Difficult cases in elderly, obese, chronic kidney disease, critical care and cirrhotic patients were reviewed. The purpose of this article is to support decision – making on dvt prevention in hospitalized medical patients.